Neurological Wilson Disease in a Young Brazilian Adult: A Case Report (Global Journal of Medical Research, 2023)
We report a rare case of Wilson s Disease with neurologic features in a 31-year-old man This disease consists of a disturbance of copper metabolism secondary to a mutation in the gene responsible for encoding the tissue transporter and the enzyme that incorporates the excess element into bile generating toxic accumulation in the liver cornea and central nervous system According to his wife the patient had been treated for an unspecified mood disorder The clinical picture was characterized by depressive mood anhedonia and anxiety He had his first seizure episode on December 3rd 2021 He progressed with dysarthria ataxic gait dystonia of the right-hand flexor muscles and intermittent urinary incontinence Marked worsening was observed after the diagnosis of COVID-19 in February 2022 At the clinical evaluation on March 24th risorius muscle dystonia risus sardonicus resting tremor and Kayser Fleischer rings at slit-lamp examination was also noted
Keywords: wilson disease inborn errors in metal metabolism dystonia